Laporan Kasus dan Tinjauan Pustaka Giant Cell Tumor of Tendon Sheath - Timotius Benedict Djitro; Dyonesia Ary Haryanti; Kidyarto Suryawinata; Iwan Irawan Karman (Majalah Patologi Indonesia, 2020)
BackgroundGiant cell tumor of tendon sheath (GCTTS) is the 2nd most common tumor in the hand but is relatively rare ineveryday practice. The tumor has a tendency to develop in women aged 30-50 years and has no specific symptoms.This characteristic made GCTTS difficult to distinguish clinically from other tumor occurring mainly in the hand. Inaddition, high recurrence rate also made these tumors often reappear despite having been excised. As such,preoperative histopathologic examination is important in enforcing the diagnosis so that appropriate steps can betaken to suppress the recurrence rate of this tumor